2018
DOI: 10.1155/2018/5896901
|View full text |Cite
|
Sign up to set email alerts
|

HIV-TB Coinfection among 57 Million Pregnant Women, Obstetric Complications, Alcohol Use, Drug Abuse, and Depression

Abstract: Objective HIV and tuberculosis represent diseases of major public health importance worldwide. Very little is known about HIV-TB coinfection among pregnant women, especially from industrialized settings. In this study, we examined the association between TB, HIV, and HIV-TB coinfection among pregnant mothers and obstetric complications, alcohol use, drug abuse, and depression. Method We examined inpatient hospital discharges in the United States from January 1, 2002, through December 31, 2014. We employed mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…Many obstacles were defined that prevented access to ART such as depression, cognitive disorders, alcohol abuse, substance abuse, lack of social support, lack of uninterrupted social security, interruptions in the drug supply, treatment fatigue, number of pills and drug side effects [10,[17][18][19]. Although novel antiretroviral drugs are easier to use and have fewer side effects compared to historical drugs, full adherence rates globally are still lower than 70 % [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many obstacles were defined that prevented access to ART such as depression, cognitive disorders, alcohol abuse, substance abuse, lack of social support, lack of uninterrupted social security, interruptions in the drug supply, treatment fatigue, number of pills and drug side effects [10,[17][18][19]. Although novel antiretroviral drugs are easier to use and have fewer side effects compared to historical drugs, full adherence rates globally are still lower than 70 % [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the psychiatric morbidity among PLWH showed that 24% of the cases had mood disorders, 19% had major depressive disorder, 1% had anxiety disorder, 7% had adjustment disorder, 1% had psychotic disorder and 17% had a history of substance abuse [15]. Depression, cognitive disorders, alcohol and substance abuse have been reported to be associated with poor prognosis in addition to ART non-adherence [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A Tuberculose (TB) está entre as infecções mais frequentes em pessoas com Vírus da Imunodeficiência Humana (HIV), (1) sendo difícil de ser diagnosticada, em virtude da própria imunodeficiência, que acarreta a possibilidade de modificação da apresentação radiológica e clínica, bem como a menor sensibilidade à baciloscopia. A TB pode acometer a pessoas com HIV em diferentes estágios da doença, embora seja mais incidente naqueles com supressão imunológica, ocasionando maior risco de progressão para o estágio final da doença e de morte.…”
Section: Introductionunclassified
“…A multirresistência dificulta o controle, a prevenção e o tratamento da doença, o que pode ocasionar a piora do quadro clínico da pessoa, aumentando, assim, os riscos de morbidade e mortalidade. (1) Diante disso, a Organização Mundial de Saúde (OMS) lançou, como objetivo global, eliminar a endemia da TB, reduzir em 90% o número de mortes e 80% das taxas de incidência até 2030, de modo a erradicar a doença até 2050. Além de lançar estratégias que objetivam apoiar essas metas, como Fim da TB (End TB Strategy).…”
Section: Introductionunclassified
“…Tuberculosis (TB) is a major cause of human infectious diseases especially in developing countries [1]. TB leads to one of the public health problems in the area of the epidemic of HIV/AIDS [1,2]. A number of TB cases have been detected yearly [1].…”
Section: Introductionmentioning
confidence: 99%